EU AND RUSSIA: WHAT “AND” MEANS? - Lopata, Raimundas (Politologija, 2015)
In the article, the EU and Russia relations are analyzed as paying specific attention to the conceptual and practical weight provided for the conjunction “and” when EU–Russia relations are interpreted and practically constructed in the West. The answer which is in common use – these relations are intellectually based and practically shaped according the engagement doctrine – is known well. However, the common answer does not eliminate the problem why the perspective of the practical application of engagement toward Russia is still under dispute in the West? The article proceeds to revealing the specifics of the Western attitudes in regard to engagement with Russia and theirs correlation with the cultural-political identities of engagement’s participants. The conjunction “and” emphasizing the EU–Russia relations is interpreted in three ways: optimistically, equably and skeptically. Optimists, moderates and skeptics are more “ideal”, resumptive entitlements characterizing the Western interpreters of engagement according theirs believe in the success of the practical implementation of the doctrine. Generalizing the optimists it is worth to note that they trust the strategy of engagement and believe that is possible to harmonize two-tracks policy (temptation and intimidation) toward Russia. Moderates believe in the future of engagement in long term perspective same as optimists. They link the success of engagement with the perspective of strategic consolidation of the EU directed by old-member states of the EU to the expense of the interests of the new-comers. Skeptics are inclined to emphasize the lack of values dimension in the EU–Russia relations. According to skeptics, the lack creates the opportunity for the mutual cooperation and for power struggle seeking to overreach each other and to prevail over each other. The diversity of interpretations is stimulating by the nodus of factors (history, values, pragmatic interests) which is still affects the EU and Russia relations as well as different attitudes toward the perspectives of co-operation in the future. The very important source of the diversity is the difference in disparity of position regarding the geopolitical development of Eurasia. The article ends with the conclusion that the direction of the EU and Russia engagement will be strongly influenced by the reciprocal attempts to define theirs own cultural-political identities.